Diseases caused by mitochondrial DNA mutations - Matiiuk, V. (Scientific Progress & Innovations, 2022)
This article highlights data on diseases caused by mitochondrial DNA mutations. The purpose of the review was to reveal existing diseases that arise as a result of mtDNA mutations. Mitochondrial diseases are diseases that are most often caused by genetically determined structural and functional disorders of mitochondria, and as a result, the energy supply of cells is disrupted. All mitochondrial diseases are transmitted through the maternal line, so if mutations are detected in time, they can be blocked and the further inheritance will be stopped. It is suggested that the role of mitochondrial DNA in certain diseases began to develop rapidly in 1988 when the first mutations in mitochondrial DNA were discovered. To understand the course and development of mitochondrial DNA, it is necessary to understand the structure and functional properties of the mitochondrial cell. MtDNA is a circular DNA molecule and is localized in mitochondria. Such organelles can replicate, transcribe, and translate their own DNA independently of nuclear DNA. Mitochondrial DNA can mutate more than 10 times more often than nuclear DNA. MtDNA has no protective functions against the phenomena of mutations. A mitochondrial cell can contain both mutant DNA and normal DNA. In genetics, such a condition is called heteroplasmy, which allows the survival of a lethal mutation. Single deletions, large deletions, and multiple deletions that are transmitted autosomally and have different phenotypic manifestations are the primary cause of the development of mitochondrial diseases. Scientists also identify systemic manifestations of mitochondrial DNA mutations. they include endocrine manifestations (diabetes), neurological diseases, gastrointestinal manifestations (acid-alkaline imbalance), and pulmonary manifestations (myoclonic epilepsy, hypoventilation abnormalities). Several main principles of treatment of mitochondropathies are distinguished: following a diet; additional introduction of cofactors involved in enzymatic reactions of energy metabolism (thiamine, riboflavin, nicotinamide, lipoic acid, biotin, carnitine); prescription of drugs, capable of carrying out the function of transferring electrons in the respiratory chain (vitamins K1 and K3, ascorbic acid).